Effects of using e-learning as a substitute for traditional education in the time of Corona (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to: identify the effects resulting from the use of e-learning as a substitute for traditional education in the time of Corona from the perspective of the teachers of the University of Basra. It also aims to identify the statistically significant differences in their opinions in the light of their specialization (Scientific – Humanities).The research sample consisted of (1000) teaching specializations (Scientific, Humanities).  An open electronic questionnaire was presented to a number of teachers in different universities and different disciplines to elicit the pros and cons of e-learning. In light of their answers and review of the literature, a questionnaire composed of (45) items was prepared. This questionnaire was presented to a number of arbitrators to determine its validity whereby some of the paragraphs were deleted and modified. Therefore, the questionnaire in its final form consisted of (38) paragraphs. The internal consistency of its paragraphs was also determined, and its stability was established by re-testing, where the stability reached (0.84). After that, the questionnaire was applied to the basic research sample. The research reached a number of results, the most important of which are the following:• There are many negative effects that resulted from the use of e-learning as a substitute for traditional education in the time of Corona. The most severe effects were concentrated in paragraph No. (25) on the scale (Equating between the levels of students (good, average and poor) because of the quality of the questions used, the ease of cheating, and the lack of monitoring with the open time.) which came first with a weighted mean of (1.90) and a weight percentage of (95%).• There are no statistically significant differences at the level (0.05) between the teachers’ views on e-learning in terms of its negative and positive effects according to the specialization (Scientific – Humanities).